Circulating angiostatin serum level in patients with systemic sclerosis - Gerlicz-Kowalczuk, Zofia; Dziankowska-Zaborszczyk, Elzbieta; Dziankowska-Bartkowiak, Bożena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction : Systemic sclerosis (SSc) is achronic connective tissue disease characterized by microangiopathy with inadequate angiogenesis. Angiostatin (AS) is a potent antiangiogenic factor specifically inhibiting proliferation and inducing apoptosis of vascular endothelial cells. Aim : To evaluate the level of angiostatin in the serum of patients with SSc. Material and methods : Serum levels of AS were measured in 20 SSc patients and 12 healthy controls. Results : A statistically significant difference in the serum levels of AS in SSc patients was observed compared to the control group (636.51 vs. 869.20 ng/ml; p = 0.012). Significant correlations between limited and disseminated SSc (lSSc/dSSc) were not found, however, a difference between lSSc and the control group was demonstrated (620.00 vs. 869.20 ng/ml; p = 0.011). The serum level of AS was not associated positively with organ changes caused by SSc. However, a statistically significant lower serum level of AS was observed in patients with SSc and no esophageal (p = 0.008) or pulmonary changes (p = 0.007) compared to the control group. Conclusions : Our results reveal significant differences in AS level in SSc patients compared to the healthy controls, and suggest that a low level of AS may occur as a result of impaired angiogenesis.